Support for people with long-term neurological conditions in rural English communities. (2nd May 2019) - Toze, Michael; Sisson, Kelly; George, Thomas; Ray, Mo
Abstract : Almost one-fifth of the population in England lives in rural areas. Compared to urban populations, the rural population is older and faces greater difficulties in accessing medical services. At the same time, healthcare teams in rural areas face particular challenges in recruiting and retaining staff, travelling between patients and keeping specialised knowledge up-to-date. Drawing upon a recent health needs assessment for people living with long-term neurological conditions in a rural English county, as well as a broader review of the literature, this paper considers the challenges of rurality and discusses potential solutions. Technological and community-based responses have often been suggested as responses to challenges of rurality. However, there is likely to be a need for up-front investment of resources and careful consideration of individual and community needs before these solutions can be applied to rural neurological care.